Analysis review on spatial and transform domain technique in digital steganography - Farah Qasim Ahmed Alyousuf; Roshidi Din; Alaa Jabbar Qasim (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents several techniques used in digital steganography in term of spatial and transform domain. Additionally, it analyses the performance and the metric evaluation of the techniques used in digital steganography based on spatial and transform domain. This paper aims to identify the main mediums of digital steganography, which are image-based, video-based and audio-based, in order to recognize the various techniques used with them. As a result, the primary technique used in the digital medium was LSB technique in the spatial domain, while in the transform domain, the main technique used was differentiated between DTC and DWT. Meanwhile, the common domain utilized in digital steganography was the spatial domain due to its simplicity and high embedding capacity. The future efforts for this paper will be considering the feature based in text steganography.